The Application of Spiritual-Based Adult Education Methods to Increase Students' Independent Learning Motivation - Panjaitan, Rizki Ajhari; Eliasa, Eva Imania (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to improve students' enthusiasm for independent learning through the application of the spiritual andragogy approach in the Islamic Educational Guidance and Counseling Study Program, Faculty of Tarbiyah and Teacher Training, State Islamic University of North Sumatra. The methodology used is descriptive qualitative, with data collection from six lecturers and forty students through interviews and questionnaires. The main findings indicate that the application of the spiritual andragogy approach that integrates Islamic beliefs can significantly improve students' motivation and learning outcomes. The benefits of this approach lie in its ability to facilitate learner-centred learning, value relevant experiences, and encourage independent learning. However, this study also identified several challenges, including the diversity of student backgrounds, internet connection problems, and difficulties in supervising their activities. The recommendations produced aim to optimize the use of the spiritual andragogy method in higher education, with a focus on improving student learning outcomes.